Research Mapping on Batik in Scopus-Indexed Publications - Aulianto, Dwi Ridho; Wardian, Wendia Kusuma; Auliani, Wulan Suci Intan (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
This research aims to survey the field of batik-related studies within the Scopus database. The chosen methodology involves bibliometric analysis, utilizing the keyword